EKSISTENSI PERMAINAN TRADISIONAL YANG MEMILIKI MANFAAT BAGI ASPEK PERKEMBANGAN ANAK USIA DINI DI RA KECAMATAN TEGALDLIMO - Moh. Anas Syamsudin (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
As time goes by, traditional games are rarely played by early childhood. Traditional games have been replaced by modern games. In this modern era, it is very rare for young children to play traditional games in their environment. The existence of traditional games is mostly done in schools with teacher guidance. The purpose of this study was to determine the number of traditional games that are still used in learning at RA Tegaldlimo District, classify how to play, and classify their functions for aspects of child development according to age levels. The method used is descriptive qualitative with observation and interview data collection techniques. The results show that there are 19 types of traditional games that are still used in RA Tegaldlimo District. Based on how to play, there are 12 traditional games that are played without songs, and 7 traditional games that use songs. Based on age match, there are 16 traditional games that are suitable for Kinder A, and 19 traditional games for Kinder B. Based on the aspects that can be stimulated, all the traditional games in RA Tegaldlimo can stimulate 6 aspects of children's development.